2017
DOI: 10.1016/j.freeradbiomed.2017.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Arctic ground squirrel resist peroxynitrite-mediated cell death in response to oxygen glucose deprivation

Abstract: Cerebral ischemia-reperfusion (I/R) injury initiate a cascade of events, generating nitric oxide (NO) and superoxide(O2•−) to form peroxynitrite (ONOO−), a potent oxidant. Arctic ground squirrel (AGS; Urocitellus parryii) show high tolerance to I/R injury. However, the underlying mechanism remains elusive. We hypothesize that tolerance to I/R modeled in an acute hippocampal slice preparation in AGS is modulated by reduced oxidative and nitrative stress. Hippocampal slices (400 microns) from rat and AGS were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…An in vitro model of OGD/reperfusion has been used for studying the mechanisms of neuron death after ischemic stroke. NMDA (N-methyl-d-aspartic acid) mediated excitotoxicity, and oxidative stress were reported to be involved in neuron death [28][29][30]. However, the roles of astrocytes in ischemic brain injury-induced excitotoxicity have been seldom investigated before.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro model of OGD/reperfusion has been used for studying the mechanisms of neuron death after ischemic stroke. NMDA (N-methyl-d-aspartic acid) mediated excitotoxicity, and oxidative stress were reported to be involved in neuron death [28][29][30]. However, the roles of astrocytes in ischemic brain injury-induced excitotoxicity have been seldom investigated before.…”
Section: Discussionmentioning
confidence: 99%
“…3D), which is likely an indicator not only of outer mitochondrial membrane (OMM) but also IMM damage following ischaemia. Importantly, others have directly correlated this cytochrome c response to the degree of membrane damage using LDH leakage assays in Sprague Dawley rat brain (Fernández-López et al 2005;Bhowmick & Drew, 2017). Thus, in NMRs, a stable cytochrome c-induced O 2 consumption response across treatment groups indicates that the IMM integrity is well-maintained, whereas the decreased capacity of complex II-linked OXPHOS might be due to slight damage to the OMM (Fig.…”
Section: Ischaemia-induced Deficits In Mitochondrial Respiration Are Mild In Nmr Cortical Brain Tissue Compared With Micementioning
confidence: 96%
“…Interestingly, this study demonstrated that tolerance to oxygen glucose deprivation in AGS occurs independent of hibernation season and persists in conditions mimicking ischemia-reperfusion such as following depletion of ATP, glutamate excitotoxicity, and acidosis. As in hypoxia preconditioning, reduced release of ROS and reactive nitrogen species in response to oxygen glucose deprivation are key factors underlying reduced cell death in AGS [54]. While the bioenergetic feats of AGS hibernation are notable, perhaps even more astounding is the rapid dendritic regrowth and synaptic rebuilding accompanying each IBA [55].…”
Section: Pathways Of Resilience: Lessons From the Laboratory Nature And The Clinical Realmmentioning
confidence: 99%